Resveratrol may dose-dependently modulate nephrin and OTULIN levels in a doxorubicin-induced nephrotoxicity model - Yalcin, Tuba; Kaya, Sercan; Kuloglu, Tuncay (Taylor & Francis Ltd, 2024)
One of the most important side effects of Doxorubicin (DOX), a chemotherapeutic agent, is nephrotoxicity. The purpose of this study is to determine whether different doses of natural polyphenol Resveratrol (RSV) show antioxidative, anti-inflammatory or antiapoptotic effects in kidney tissue in DOX-induced nephrotoxicity and to detect how nephrin and OTULIN levels are affected in this process. A total of six equal groups made up of the 42 Sprague-Dawley rats utilized in the study (n = 7) were randomly assigned. Except for the control group (no treatment), all treatments were given intraperitoneally to the DOX (15 mg/kg), DOX + RSV I (15 mg/kg DOX+ 1 mg/kg/day RSV), DOX + RSV II (15 mg/kg DOX+ 5 mg/kg/day RSV), RSV I and RSV II groups. Kidney tissues taken from rats sacrificed on the fifteenth day were analyzed biochemically, histologically and immunohistochemically. Accordingly, it was determined that nephrin and OTULIN levels decreased in kidney tissue in DOX-induced nephrotoxicity. Furthermore, DOX caused oxidative stress, inflammation, and apoptosis, as well as histopathological changes in kidney tissue. However, it was observed that DOX-induced changes were regulated by RSV application. RSV was demonstrated to have antioxidant, anti-inflammatory and anti-apoptotic properties in dose-dependent DOX-induced nephrotoxicity. RSV may exert nephroprotective effects by modulating DOX-induced altered nephrin and OTULIN levels.
Keywords: OTULIN; nephrin; doxorubicin; resveratrol; nephrotoxicity